2008
DOI: 10.1154/1.2996511
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray powder diffraction data of atorvastatin

Abstract: X-ray powder diffraction data collected in transmission and high-throughput geometries were used to analyze form I of atorvastatin. The X-ray wavelength of the synchrotron radiation used in this study was determined to be λ=1.3771 Å. Form I of atorvastatin was found to be triclinic with space group P1 and unit cell parameters a=5.4568(2) Å, b=9.8887(4) Å, c=30.3091(9) Å, α=76.801(3)°, β=99.177(5)°, γ=105.318(5)°, V=1527.1(1) Å3, Z=1, and M=1209.41 g mol−1 Alternatively, another unit cell dimension can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The powder pattern of this study is an excellent match to PDF entry 00-062-1582 (Antonio et al, 2008) and to that reported in US Patent 5,969,156 (Briggs et al, 1999), indicating that our sample is representative of ACT Form I (Figure 3). The agreement of the two density functional theory (DFT) geometry optimizations is good but not perfect (Figure 4).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The powder pattern of this study is an excellent match to PDF entry 00-062-1582 (Antonio et al, 2008) and to that reported in US Patent 5,969,156 (Briggs et al, 1999), indicating that our sample is representative of ACT Form I (Figure 3). The agreement of the two density functional theory (DFT) geometry optimizations is good but not perfect (Figure 4).…”
Section: Resultssupporting
confidence: 85%
“…4471, b = 9.8902, c = 29.5984 Å, α = 95.846, β = 94.206, γ = 105.275°, and V = 1521.87 Å 3 . This is very close to the "alternate" unit cell of Antonio et al (2008), and its volume corresponds to Z = 1. A reduced cell search in the Cambridge Structural Database (Groom et al, 2016) yielded no hits.…”
Section: Methodsmentioning
confidence: 61%
See 3 more Smart Citations